PENGARUH MOTIVASI KERJA DAN KINERJA KARYAWAN TERHADAP DISIPLIN KERJA PADA PT. CIPTA NIAGA SEMESTA (MAYORA GROUP) DI LAMPUNG TENGAH - Safrudin, Safrudin; Suhada, Bambang; Sigalingging, Marhaban (Universitas Muhammadiyah Metro, 2025)
Work discipline is a reflection of good human resources and is able to encourage the development of the agency or company it manages, so in this study the researcher examines the work discipline of employees at PT. Cipta Niaga Semesta (Mayora Group) in Central Lampung. The aim of this research is to examine both partially and simultaneously the relationship between work motivation and employee performance regarding work discipline. The design of this research uses a quantitative method that is refined with selected indicators that are described by the researcher into a questionnaire that is distributed to 50 representative employees based on formula calculations and sampling techniques using Stratified Random Sampling. And data analysis techniques use instrument validity, reliability, and multiple linear regression tests with decisions using partial t, simultaneous f test, and coefficient of determination. The results of this research prove that work motivation and employee performance can form the basis for strong work discipline in an organization. Organizations that motivate employees, provide recognition for good performance, and support skill development can create a positive work environment that fosters work discipline. On the other hand, employees who are motivated and have good performance tend to be more disciplined in carrying out their duties efficiently.